Congenital malformations in Oreochromis niloticus larvae during incubation in hatchery - Baltazar Guerrero, Paul Martin (2020)
Twelve congenital malformations observed during the artificial incubation process of Oreochromis niloticus embryos in hatchery are reported and described, identifying possible causes and linking them to biological mechanisms of normal embryonic development.